Inhibition of serotonin transporter expression by C/EBPβ in LPS-activated macrophage cells (HD11). Issue 4 (May 2015) - Zimmermann, Katrin; van Phi, Valerie D; Brase, Angela; Phi-van, Loc
Serotonin (5-hydroxytryptamine; 5-HT) transporter (5-HTT) is involved in inflammation and the stress response. In this study, we examined the regulation of 5-HTT expression in macrophage HD11 cells in response to bacterial LPS. Long-term exposure of cells to LPS (6–18 h) produced a decrease in 5-HTT mRNA expression. Accordingly, reduced 5-HTT activity measured by 5-HT uptake was also observed in LPS-treated HD11 cells. Moreover, LPS treatment, as well as co-transfection with an expression vector encoding the chicken CCAAT/enhancer binding protein beta (C/EBPβ), resulted in inhibition of 5-HTT promoter activity. Indeed, sequence analysis revealed several C/EBPβ binding motifs in the upstream region of the 5-HTT gene, which specifically interacted with C/EBPβ both in an in vitro band shift assay and in living HD11 cells. The C/EBPβ binding was activated in cells treated with LPS. The role of C/EBPβ in LPS inhibition of 5-HTT expression was further confirmed by small interfering RNA interference, which demonstrated that knockdown of endogenous C/EBPβ attenuated the inhibition of 5-HTT expression in LPS-treated cells. Taken together, the results suggest that C/EBPβ plays a critical role in regulating the 5-HTT gene in macrophages in response to pro-inflammatory stimuli.